2022
DOI: 10.2514/1.j060799
|View full text |Cite
|
Sign up to set email alerts
|

Concave Bump for Impinging-Shock Control in Supersonic Flows

Abstract: to initiate your request. See also AIAA Rights and Permissions www.aiaa.org/randp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
5
1
Order By: Relevance
“…Both the experimental results (blue dots) and numerical results (triangles) of the current study show a common and distinct correlation between the scaled plateau pressure and the scaled interaction strength. Additionally, particularly valuable are the data from an earlier numerical study (Schülein, Schnepf & Weiss 2021) (crosses) in a wide Mach number range of , which impressively confirm the empirical correlation. The scatter of the data is relatively low, especially when distinguishing between 2-D simulations and 3-D simulations.…”
Section: Resultssupporting
confidence: 59%
“…Both the experimental results (blue dots) and numerical results (triangles) of the current study show a common and distinct correlation between the scaled plateau pressure and the scaled interaction strength. Additionally, particularly valuable are the data from an earlier numerical study (Schülein, Schnepf & Weiss 2021) (crosses) in a wide Mach number range of , which impressively confirm the empirical correlation. The scatter of the data is relatively low, especially when distinguishing between 2-D simulations and 3-D simulations.…”
Section: Resultssupporting
confidence: 59%
“…To achieve the first goal, an appropriate turning angle θ E of EC (see figure 4a) needs to be selected, because the SCB essentially works through the beneficial interaction between incident shock and expansion fan generated by the EC. Schülein (2022) proved that the SCB had the best control effect when the θ E was equal to or slightly greater than the incident shock deflection angle. In this paper, the deflection angle θ w of the IS has been solved by the inviscid theory.…”
Section: Discussion Of the Shock Control Strategymentioning
confidence: 97%
“…As introduced in § 1, the SCB is a passive control device with a low-drag profile and good control effect. In particular, the concave-shaped SCB proposed by Schülein (2022) can split strong incident shock into a weaker multi-wave system, which has great potential to reduce the pressure/heating peaks. Inspired by the results of Schülein, a shock control strategy of placing a concave SCB on the shock impingement is proposed.…”
Section: Discussion Of the Shock Control Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The results suggested that the onset of flow separation strongly depends on the Mach number and the wedge angle, where an increase in the Mach number has a tendency to postpone the onset of flow separation at a constant deflection angle, which in turn, leads to a reduction of the separation length. More recently, Schülein et al [43] employed numerical simulations and experiments to investigate the use of a concave bump for impingingshock control considering a wide range of Mach numbers and wedge angles. To verify the effectiveness of the flow control strategy, the authors also studied a baseline configuration without a bump, where similarly to Souverein et al [42], they observed that the size of the separation bubble decreases with increasing Mach number.…”
mentioning
confidence: 99%